Transcriptional Regulation of Seprase in Invasive Melanoma Cells by Transforming Growth Factor-β Signaling - Tulley, Shaun (American Society for Biochemistry and Molecular Biology, 2014)
The tumor invasive phenotype driven by seprase expression/activity has been widely examined in an array of malignant tumor cell types; however, very little is known about the transcriptional regulation of this critical protease. Seprase (also named fibroblast activation protein-α, antiplasmin-cleaving enzyme, and dipeptidyl prolyl peptidase 5) is expressed at high levels by stromal fibroblast, endothelial, and tumor cells in a variety of invasive tumors but is undetectable in the majority of normal adult tissues. To examine the transcriptional regulation of the gene, we cloned the human seprase promoter and demonstrated that endogenous seprase expression and exogenous seprase promoter activity are high in invasive melanoma cells but not in non-invasive melanoma cells/primary melanocytes. In addition, we identified a crucial TGF-β-responsive cis-regulatory element in the proximal seprase promoter region that enabled robust transcriptional activation of the gene. Treatment of metastatic but not normal/non-invasive cells with TGF-β1 caused a rapid and profound up-regulation of endogenous seprase mRNA, which coincided with an abolishment of the negative regulator c-Ski, and an increase in binding of Smad3/4 to the seprase promoter in vivo. Blocking TGF-β signaling in invasive melanoma cells through overexpression of c-Ski, chemically using SB-431542, or with a neutralizing antibody against TGF-β significantly reduced seprase mRNA levels. Strikingly, RNAi of seprase in invasive cells greatly diminished their invasive potential in vitro as did blocking TGF-β signaling using SB-431542. Altogether, we found that seprase is transcriptionally up-regulated in invasive melanoma cells via the canonical TGF-β signaling pathway, supporting the roles of both TGF-β and seprase in tumor invasion and metastasis.